Why Do School Staff Sometimes Fail to Report Potential Victimization Cases? A Mixed-methods Study - Greco, Ana M. (Journal of interpersonal violence, 2022)
Schools are in a position to connect children and adolescents suspected of being victims of violence with an external source of support by making referrals to external agencies. However, several studies have identified obstacles that hinder early reporting among school staff members. Very few studies have applied a mixed-method approach to try to understand this sensitive issue. The current study used this approach to analyze to what extent the students suspected of being victimized match the ones reported by active school staff members in Spain (n = 453, 83.5% females, age: M = 42.23, SD = 9.46). We classified the reasons given for not reporting the potential victimization cases encountered and made comparisons to determine whether there were differences in the level of knowledge, or in the sociodemographic characteristics, of respondents who gave different reasons for not reporting. Although 73.5% of school staff members had detected at least one potential case, 40.8% of them referred it to an external agency. The most common reasons for lack of reporting included deciding not to do so once concerns had been shared within the school and believing that one must be certain or that only serious violence should be reported. The findings of this study may help to further understand the decisions not to report certain suspicions of potential victimization cases to external agencies by school staff. There is an urgent need to raise awareness about the duty to report these concerns to external agencies, even in the absence of agreement from the school management team. Members of school staff need to be strongly encouraged to become familiar with the existing protocols.